From the television to the extended television after Marshall Mcluhan - Islas Carmona, Octavio (2016)
This text is composed of 4 sections. In the first one, I recovered the emotive speech made by WilburSchramm about the first television broadcasting carried out on January 26th 1926 by John Logie Bairdin order to support the relevance of the term “Age of television”. The television is actually considered asthe emblematic media in the “Age of electricity”. In the second section, I studied the thesis developed byMarshall McLuhan about the so-called “shy giant”. At the beginning of 1960s, the television captivatedMarshall McLuhan. From a particular ecumenical perspective, the Canadian researcher believed thatthe television would restore the sensitive balance, thus favoring the transition to the “global village”. Asthe years went by, his optimism about the television started to vanish, and McLuhan adopted a morecritical position, similar to Neil Postman’s, against the television. In the third section, I stood out thatMcLuhan anticipated the media convergence; then, I explained his Tetrada and pointed out the wayBob Logan (2010) used it to make an analysis of the television and the cable television. Finally, in thefourth section, I recovered the Tetrada from McLuhan to study some of the most interesting modalitiesof extended television: Youtube, Netflix and Internet Protocol Television (IPTV).